A Frequency Selection Method Based on the Pole Characteristics - Songyan Yang; Weibo Deng; Qiang Yang; Guangxin Wu; Ying Suo (International Journal of Antennas and Propagation)
Due to the heavy jamming band of high frequency, frequency selecting strategies are serious issues for the system designed to achieve its best performance. Pole is independent of the direction and polarization of the incident wave, but the residue corresponding to the pole is related to the direction and polarization of the incident wave. And the value of residue is proportional to the value of the pole. This paper chooses the frequency which can maximize the residue in the high-frequency band as the optimal frequency for accurate extraction. The simulation result of a large number of ship targets shows remarkable rise in average recognition rate by using this method, compared with the average recognition rate of randomly selected frequency.